Conflict of Interest on Public Procurement Management in Uganda - Adoko Obicci, Peter (International Research Journal of Business and Management, 2015)
Conflict of interest though a very popular constructs in management literature has not had many studies conducted on it. The objective of this article is to investigate the effects of conflict of interest on public procurement management in the Public Sector in Uganda. This research was carried out by measuring data gathered from five Likert scale on a self administered questionnaire to 228 employees from the public sector. Random sampling technique was used to answer the instrument of the study. Computer software (SPSS Ver. 16) was used to analyze the collected data based on descriptive statistics, Pearson Correlation Co-efficient and regression analysis. Major findings showed interpersonal, intra-group and inter-group conflicts of interest strongly correlated with public procurement management with respectively correlation coefficients of 0.638, 0.758 and 0.641. The study was limited to Uganda’s public sector but further study should consider being longitudinal in nature. Implicitly there should be focus on eradicating the evils of conflict of interest in procurement management. Since there is still limited research in this field, this article makes it contribution by providing information that is relevant for filling the gap, hence useful for policy makers, academicians, procurement professionals, and researchers.
Keywords: Conflict of interest; Public Procurement Management